RECOMMENDATIONS TO STRENGTHEN THE ROLE OF LADY HEALTH WORKERS IN THE NATIONAL PROGRAM FOR FAMILY PLANNING AND PRIMARY HEALTH CARE IN PAKISTAN: THE HEALTH WORKERS PERSPECTIVE - Afsar, Habib Ahmed; Younus, Muhammad (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was planned to assess the strengths and weakness of the National Program for Family Planning and Primary from the Lady Health Workers (LHW) perspective. We conducted this study in order to develop recommendations for strengthening LHWs’ role in Primary Health Care (PHC) in Pakistan in consultation with the health workers. Methods: A qualitative study, based on key informant interviews, was carried out in Karachi, Pakistan. A total of 20 workers were interviewed. Analysis was carried out by grouping similar responses in a matrix and then analysis with reference to context. Results: Motivations for joining program included financial benefits, convenient timings and an opportunity to serve humanity. Training was deemed satisfactory but clinical training was resented because of doctors’ attitudes. Further training needs identified included basic information about common ailments, reproductive issues and basic clinical skills. Major strengths of the program mentioned included provision of services at grass root level, reinforcement of health messages and the community acceptability of workers. Weaknesses mentioned included the contractual nature of job, low salaries, irregularity of payment, no career development and poor logistical support. Conclusion: Giving LHWs permanent government employee status and a raise in salary may strengthen the workers functions. Eligible LHWs should be given incentives (skills, career development, financial). The community must be educated about assigned role and responsibilities of LHWs and patient referral system by the LHW needs to be strengthened. The valuable role of LHWs in PHC in Pakistan must be acknowledged and further improvements pursued. Key words: Lady Health Workers; Primary Health Care; Pakistan